Meningkatkan Kemampuan Pamong Desa Ketawang Mengelola Arsip Sistem Kronologis - Rr Chusnu Syarifa Diah Kusuma; Suhartanto Suhartanto; Mochamad Hanafi; Joko Kumoro (Jurnal Pemberdayaan Umat, 2023)
Purpose: The community service aims is to provide training to village officials in managing village archives. Thus, the Ketawang Village office implements a chronological system archive management. Methodology: The community service uses the lecture and discussion method, training, and evaluation of village officials. Lectures and discussions to provide knowledge and understanding, training to provide technical skills, and evaluations to monitor and assess skills in managing village archives. Results: The results of the community service increase the understanding and management of village archives by village officials. Participants are able to explain planning, execution/implementation, classification, and benefits of village archives. The target of serving 30 village officials, 28 capable of managing village archives. Conclusions: Devotion can be concluded has been carried out properly. Participation of participants is 100% of the target of 30 village officials. The understanding and management of village archives is at the understanding level, but at the very understanding level it needs to be improved. Limitations: The limitations of dedication are the diverse backgrounds of the participants (ages and positions), so they have to be slow in delivering materials and training and the Covid-19 pandemic which has to pay attention to health protocols. Contribution: The benefits of dedication, as a forum for village officials to learn archive management, as a form of implementing the tri dharma, and forming village officials who are aware of archives.